PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 008 SUNGAI SEGAJAH KECAMATAN KUBU - Saragih, Nurdiyah; Antosa, Zariul; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Classroom action researchwas conducted because of the low sciencelearning outcomes of students with an average of 53 caused by a lack of interestin learning science. To improve science learning outcomes in class V 008 RiverElementary School Segajah Kubu district academic year 2013/2014 then appliedinquiry learning model. This study was conducted from April to June 2014subjects were students of class V, which amounts to 32 people. Average studentlearning outcomes in the first cycle of daily test is 69.21 with either category.While on the second cycle of daily test students increased to 76.25 with bothcategories. While the average activity for teachers in the first cycle is 62.5 firstmeeting with both categories, at the second meeting increased to 75 with eithercategory. While in the second cycle to the fourth meeting of the increased activityof 79.2 teachers with excellent category, the fifth meeting of the 87.5 with theexcellent category. While the activities of the students at the first meeting of thefirst cycle is 62.5 with a good category, at the second meeting of increase rose to79.2. While in the second cycle to the fourth meeting of the student activityincreased 83.3 with excellent category, the fifth meeting of the 87.5 with theexcellent category, from this study it can be concluded that the application ofinquiry learning model to improve learning outcomes fifth grade elementaryscience students 008 River country Segajah Kubu district.Keywords : Model of inquiry learning, science learning outcomes